2021
DOI: 10.3233/jnd-200533
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Patients with Spinal Muscular Atrophy Type 1 Treated with Nusinersen

Abstract: Background Spinal muscular atrophy type 1 (SMA1) is a motor neuron disease associated with progressive muscle weakness, ventilatory failure, and reduced survival. Objective: To report the evaluation of the nusinersen, an antisense oligonucleotide, on the motor function of SMA1. Methods This was a longitudinal and observational study to assess the outcomes of nusinersen therapy in SMA1 patients using the HINE-2 and CHOP-INTEND scales. Results Twenty-one SMA1 patients (52.4% males) were included; the mean age at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Lavie et al and Ali et al identified no reduction in NIV needs 24 months post-treatment [ 36 , 43 ]. De Holanda Mendonca et al reported data on SMA1 patients with different duration of monitoring and it took 6–24 months to demonstrate a decrease in NIV support needs in only a minority of them [ 42 ]. Similarly, Kim et al were able to identify diminished NIV use by only two hours post-Nusinersen in 50% of a small cohort of patients, who were on NIV at baseline [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lavie et al and Ali et al identified no reduction in NIV needs 24 months post-treatment [ 36 , 43 ]. De Holanda Mendonca et al reported data on SMA1 patients with different duration of monitoring and it took 6–24 months to demonstrate a decrease in NIV support needs in only a minority of them [ 42 ]. Similarly, Kim et al were able to identify diminished NIV use by only two hours post-Nusinersen in 50% of a small cohort of patients, who were on NIV at baseline [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taking under consideration all patients treated with Nusinersen in all included studies who were receiving respiratory support at baseline, a reduction in ventilator settings was noted in only 7.5% of them and unchanged settings in 70.9% during monitoring for up to 24 months post-treatment initiation [ 32 , 36 , 38 , 39 , 40 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nusinersen treatment has been associated with both improvement 52,[141][142][143] and no effect 144,145 on lung function in various studies measured via FVC and need for assisted ventilation. Responses to nusinersen likely differ between SMN type and timing of intervention relative to symptom onset.…”
Section: Chest Deformity Thoracic Insufficiency and Pulmonary Healthmentioning
confidence: 99%
“…The Brazilian National Health Surveillance Agency (ANVISA) approved it in 2017 7 . Because of its inability to cross the blood-brain barrier, nusinersen is administered intrathecally in a therapeutic regimen requiring four lumbar punctures within two months and consecutive maintenance injections every four months thereafter 5,6,7,8,9 . This administration schedule has proven to be a challenge in patients with scoliosis and in those with previous spinal fusion.…”
Section: Introductionmentioning
confidence: 99%